After the gold rush: industrial re-configuration in the UK television production sector and content. (October 2019) - Doyle, Gillian; Barr, Kenny
Recent technological and market changes in the television industry appear to have transformed the corporate configurations which conduce to economic success in the production industry. As a result, many leading independent television production companies in the United Kingdom and elsewhere across Europe have become prime targets for corporate activity and many have been subject to takeover, often by the US media groups. Does this matter? Does the concept of 'national' television content still have any relevance in the digital era? Drawing on a multiple-case-study-based analysis of several UK-based television production companies over recent years, this article examines how corporate takeovers in the production sector may affect creative decision-making and impact on the nature and quality of television content. Against a background of increased investment interest from multinationals in indigenous players in the United Kingdom and across Europe, the analysis presented makes a timely and policy-relevant contribution to knowledge.